Hubungan Antara Kekuasaan Kehakiman dan Kekuasaan Pemerintahan Negara : Menuju Peradilan yang Independen dan Akuntabel - Irman Putra; Arief Fahmi Lubis (Universitas 17 Agustus 1945, 2021)
This study discusses the position and function of judicial power in Indonesia, which is seen from its development since 1959, when Indonesia returned to the 1945 to 2008 Constitution. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that this study will look at the whole of the laws and regulations that regulate judicial power since the 1945 Constitution through the Presidential Decree dated July 5, 1959 and towards a one-stop court under the Supreme Court. The study will mainly be directed at how to make the judiciary in Indonesia more independent and accountable.